2015
DOI: 10.1590/0101-60830000000038
|View full text |Cite
|
Sign up to set email alerts
|

Stress and coping in a sample of medical students in Brazil

Abstract: Background: Medical training is a stressing situation, making medical students vulnerable to psychiatric disorders, such as depression and anxiety. Objective: The study aimed to assess the prevalence of stress and coping in students of a public medical school in Brazil, comparing the groups from the first and sixth years of training. Methods: Through a cross-sectional, observational study, a sample of 232 first and sixth-year regularly registered medical students has been evaluated. Students filled a socio-dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
1
15

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 30 publications
2
18
1
15
Order By: Relevance
“…Various studies done across the world had consistently shown that there is high prevalence of stress in medical students. [14][15][16][17] The mean and SD of PSS score in our study was 17.7 and 5.5 respectively which was comparable to a study done in Tamil Nadu by Sakthivel et al with mean score as 17 and SD as 6.5. 10 However it was less than that found in a study done in Kolkatta by Chowdhury et al where the mean and SD were 29.58 and 6.6 respectively.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Various studies done across the world had consistently shown that there is high prevalence of stress in medical students. [14][15][16][17] The mean and SD of PSS score in our study was 17.7 and 5.5 respectively which was comparable to a study done in Tamil Nadu by Sakthivel et al with mean score as 17 and SD as 6.5. 10 However it was less than that found in a study done in Kolkatta by Chowdhury et al where the mean and SD were 29.58 and 6.6 respectively.…”
supporting
confidence: 86%
“…7 Also in a study done by Bassols et al in Brazil the individuals more than 20 years of age experienced more stress. 14 The reason for age acting as a predictor of stress in our study is because as age increases the volume of study also increases which imparts an additional academic burden for the students which may lead to more stress. As we have already seen in our study the final year students are experiencing more stress.…”
mentioning
confidence: 89%
“…We included 59 studies in the qualitative analysis, and 57 [28][29][30][31][32][33][34][35][36][37][39][40][41][42][43][44][45][46][47][48][49][50][51][52] studies involving a total of 18,015 medical students in the quantitative analysis (Table 1). All forest plots are available on request from the authors.…”
Section: Resultsmentioning
confidence: 99%
“…Esse autor encontrou menor incidência de estresse nos alunos do primeiro ano em relação aos demais, também concordando com nossos achados, nos quais os alunos do primeiro semestre apresentavam menos estresse que os demais 12,13 . Diferentemente, Bassols et al 7 encontraram maior nível de estresse entre alunos do primeiro ano em relação aos do último ano do curso de Medicina na Universidade Federal do Rio Grande do Sul.…”
Section: Discussionunclassified
“…A ocorrência de estresse entre estudantes de Medicina é muito frequente 7,8 . É crescente a busca do entendimento desse processo, da compreensão de suas causas e consequências.…”
Section: Introductionunclassified